Affective patterns in triadic family interactions: Associations with adolescent depression. (23rd March 2015) - Hollenstein, Tom; Allen, Nicholas B.; Sheeber, Lisa
Abstract: Affective family processes are associated with the development of depression during adolescence. However, empirical description of these processes is generally based on examining affect at the individual or dyadic level. The purpose of this study was to examine triadic patterns of affect during parent–adolescent interactions in families with or without a depressed adolescent. We used state space grid analysis to characterize the state of all three actors simultaneously. Compared to healthy controls, triads with depressed adolescents displayed a wider range of affect, demonstrated less predictability of triadic affective sequences, spent more time in and returned more quickly to discrepant affective states, and spent less time in and returned more slowly to matched affective states, particularly while engaged in a problem-solving interaction. Furthermore, we identified seven unique triadic states in which triads with depressed adolescents spent significantly more time than triads with healthy controls. The present study enhances understanding of family affective processes related to depression by taking a more systemic approach and revealing triadic patterns that go beyond individual and dyadic analyses.